Prognostic Significance of Computed Tomography Findings in Pulmonary Vein Stenosis - Laureen Sena; Ryan Callahan; Lynn A. Sleeper; Rebecca S. Beroukhim (MDPI AG, 2021)
(1) Pulmonary vein stenosis (PVS) can be a severe, progressive disease with lung involvement. We aimed to characterize findings by computed tomography (CT) and identify factors associated with death; (2) Veins and lung segments were classified into five locations: right upper, middle, and lower; and left upper and lower. Severity of vein stenosis (0-4 = no disease-atresia) and lung segments (0-3 = unaffected-severe) were scored. A PVS severity score (sum of all veins + 2 if bilateral disease; maximum = 22) and a total lung severity score (sum of all lung segments; maximum = 15) were reported; (3) Of 43 CT examinations (median age 21 months), 63% had bilateral disease. There was 30% mortality by 4 years after CT. Individual-vein PVS severity was associated with its corresponding lung segment severity (p < 0.001). By univariate analysis, PVS severity score >11, lung cysts, and total lung severity score >6 had higher hazard of death; and perihilar induration had lower hazard of death; (4) Multiple CT-derived variables of PVS severity and lung disease have prognostic significance. PVS severity correlates with lung disease severity.